A new beginning: a case for establishing a sexual and gender-based violence truth commission in South Africa - Wild, Stephanie (Department of Public Law, 2025)
Globally, civil society and the media have drawn increasing attention to alarmingly high sexual and gender-based violence (SGBV) and femicide rates. This is particularly true for South Africa, having hosted two presidential summits on the topic, having produced a national action plan (NAP) detailing intervention and prevention strategies, as well as having nationwide protests against SGBV and femicide between 2018 and 2019. This thesis hopes to contribute to existing literature regarding potential intervention and response strategies to minimise SGBV and femicide, particularly in South Africa. More specifically, this thesis seeks to determine whether the novel approach of a SGBV truth commission (TC) would be an effective method to respond to and minimise the widespread femicide and SGBV violations in South Africa. This research project is a desktop thesis, drawing on existing literature in the transitional justice (TJ), gendered transitional justice (GTJ), and radical feminism fields to determine if a TJ strategy would be appropriate in the context of an established democracy and in the context of SGBV and femicide, whether a TC in particular would be the most effective TJ strategy over a reparations programme, institutional reforms, and a SGBV tribunal, as well as whether a TC would be effective, justified, and/or necessary after the Truth and Reconciliation Commission (TRC). Ultimately, this thesis suggests that a SGBV TC, if adopting an intersectional-gendered framework and if working with the National Prosecuting Authority (NPA) to pursue criminal prosecutions, would be an effective intervention strategy to both pursue justice for SGBV and femicide victims, as well as to address the root cause, patriarchy. Ultimately, this thesis concludes that a SGBV TC could pursue restorative justice goals for victims and alleviate pressure on investigative authorities through evidence collection; promote more inclusive shared narratives on SGBV to counterbalance prolific ‘rape myths'; encourage positive changes in patriarchal attitudes/beliefs within broader society and the criminal justice system; guide the implementation of well-crafted reparations and institutional reforms. This implies that TJ strategies could be implemented not only in post-war/authoritarianism contexts, but also in countries battling pervasive SGBV and femicide levels by beginning to dismantle patriarchy.